The Unpublished Opinions of the Warren Court. - Schwartz, Bernard, the late (Oxford University Press, 2014)
An important contribution to constitutional literature, this collection of ten unpublished decisions by the Warren Court puts the decision making process of the Supreme court in a new light. By following the major changes that occur in each case from the circulation of tentative majority opinions to the final issuance of opinion, the book portrays how the justices communicate with each other and how they are influenced by each other's arguments.